Preparation, structure and magnetic characterization of Ni doped ZnO nano-particles - Dogan, N.; Bingolbali, A.; Arda, L. (ELSEVIER SCIENCE BV, 2015)
The nature of magnetism in Ni-doped ZnO magnetic nano-particles (x=0.0, 0.10, 0.15, 0.20, 0.30) are synthesized by the sol-gel technique using solutions of Ni and Zn based alkoxide which are dissolved into a solvent and a chelating agent. X-ray diffraction (XRD), Scanning Electron Microscope (SEM) and Vibrating Sample Magnetometer (VSM) were employed to understand how the Ni-doped influenced the structural and magnetic properties of the nano-crystalline ZnO particles. The grain sizes of the ZnNiO nano-particles were measured to be approximately 90 nm by means of a Scanning Electron Microscope. XRD measurements and SEM studies show that Ni-doped ZnO has wurtzite structures with NiO secondary phases. Room temperature ferromagnetism was observed for highly Ni-doped ZnO nano-particles. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Nanoparticle; Magnetic measurement; Sol-gel; Zinc oxide; ZnNiO; MECHANICAL-PROPERTIES; FERROMAGNETISM; SEMICONDUCTOR; Materials Science; Physics